Phase equilibria in the SnBi2Te4MnBi2Te4 system and characterization of the Sn1-xMnxBi2Te4 solid solutions - Orujlu, E. (Physics and Chemistry of Solid State, 2020)
The phase diagram of the SnBi2Te4-MnBi2Te4 system was established over the entire concentration range by means of differential thermal analysis and powder X-ray diffraction techniques. It was shown that the system is non-quasi-binary due to the incongruent melting character of SnBi2Te4 and MnBi2Te4 compounds, but it is stable below solidus. The formation of a continuous series of solid solutions with the tetradymite-like layered structure was observed. Due to ionic radius differences of Mn2+ and Sn2+, both unit cell parameters of solid solutions increase linearly with the increasing amount of Sn. Phase equilibria above the solidus curve cannot be completed until the SnTe-MnTe-Bi2Te3 system fully studied.